France in the South Pacific : power and politics - Fisher, Denise (ANU E Press, 2013)
Combining historical background with political and economic analysis, this comprehensive study offers vital insight into the intricate history - and problematic future - of several of Australia's key neighbours in the Pacific and to the priorities and options of the European country that still rules them.